The PAZ polarimetric radio occultation research dataset for scientific applications - R. Padullés; R. Padullés; E. Cardellach; E. Cardellach; A. Paz; A. Paz; S. Oliveras; S. Oliveras; D. C. Hunt; S. Sokolovskiy; J.-P. Weiss; K.-N. Wang; et al. (Earth System Science Data)
Polarimetric radio occultations (PROs) represent an augmentation of the standard radio occultation (RO) technique that provides precipitation and cloud vertical information along with the standard thermodynamic products. A combined dataset that contains both the PRO observable retrievals and the RO standard retrievals, the resPrf, has been developed with the aim of fostering the use of these unique observations and fully exploiting the scientific implication of having information about vertical cloud structures with an intrinsically collocated thermodynamic state of the atmosphere. This paper describes such a dataset and provides detailed information on the processing of the observations. The procedure followed at the University Corporation for Atmospheric Research (UCAR) to combine both horizontal (H) and vertical (V) observations to generate profiles equivalent to those in standard RO missions is described in detail, and the obtained refractivity is shown to be of equivalent quality compared to that from TerraSAR-X. The steps for the processing of the PRO observations are detailed, derived products such as the top of the signal are described, and validation is provided.